Hubungan Pengetahuan Terminologi Medis Petugas Koding Dengan Ketepatan Kode Diagnosis di Puskesmas Dinoyo - Zein, Eiska Rohmania Zein; Rahmawati, Nabila Yunita (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2025)
A coder's lack of knowledge of medical terminology results in inaccuracies in the diagnosis code made on medical record documents. Therefore, this study aims to analyze the relationship between knowledge of coding officers' terminology and the accuracy of the diagnosis code at the Dinoyo Health Center in Malang City. The method used in this research is quantitative with a cross sectional research design. Data processing techniques using statistical software, namely SPSS. The analysis technique used is univariate and bivariate analysis. The test used in this study was the chi-square. The sample was taken using simple random sampling technique with a probability sampling of 99 samples. The results of the relationship between the coding officer's knowledge of medical terminology and the accuracy of the diagnosis code showed a value that was not correlated, namely 0.541, with a value below 0.05, there was only a correlation between the two. The results showed that the accuracy of the diagnosis code was 43.43% incorrect and 56.56% correct, for the percentage of very good knowledge of medical terminology 16.7% and 83.3% good. It is expected to increase the accuracy of the diagnosis code in order to maintain the Dinoyo Health Center coder value.